Strategi Naratif Dalam Iklan Online: Menganalisa Pengaruh Introducing Jo & Jek Terhadap Sikap Penonton di Platform Youtube - Carlos Pingsen Pratama; Vincent So; Sunoto; Muhammad Hafiz Ivan Irawan; Jenifer Lim (Journal of Trends Economics and Accounting Research, 2023)
Currently, narrative online advertising is considered effective because it can shape consumer attitudes through beliefs, feelings (affect) and behavioral intentions. Narrative-style ads are in focus because they are able to shape consumer attitudes through interesting stories and provide useful information. The objectives of this study also include understanding how Jo&Jek's narrative ads influence viewers' perceptions of the brand. In addition, this study also revealed that demographic factors such as gender and online ad viewing habits can moderate the effects of Jo&Jek narrative commercials on viewers' attitudes, therefore the researcher took this case study using Go-Jek Indonesia's web narrative commercial titled "Introduction: Jo & Jek. This study uses a quantitative approach and uses a questionnaire to collect information from those who watched Introducing Jo&Jek. There will be 400 participants used as the research sample. In this study, a Likert scale was used for quantitative data collection, and basic linear regression analysis was conducted with the help of SPSS. The simple linear regression test results yielded the formula Y = 0.172 + 0.954X. The study found that online narrative advertising explained 57.4% of the variation in viewer sentiment, and the remaining 42.6% was influenced by other variables beyond the scope of this study. Therefore, it can be said that people's perspectives on products and services are influenced by audience attitude marketing.